The Basins in 2050: Workshop Scenarios - Cook, Simon E.; Lau, Charlotte (CGIAR Challenge Program on Water and Food, 2011)
A poster focused on different scenarios on CPWF rivers basins: Andes System of Basins, Ganges, Limpopo, Mekong, Nile and Volta